2021
DOI: 10.1371/journal.pmed.1003727
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of seasonal malaria chemoprevention (SMC) treatments when SMC is implemented at scale: Case–control studies in 5 countries

Abstract: Background Seasonal malaria chemoprevention (SMC) has shown high protective efficacy against clinical malaria and severe malaria in a series of clinical trials. We evaluated the effectiveness of SMC treatments against clinical malaria when delivered at scale through national malaria control programmes in 2015 and 2016. Methods and findings Case–control studies were carried out in Mali and The Gambia in 2015, and in Burkina Faso, Chad, Mali, Nigeria, and The Gambia in 2016. Children aged 3–59 months presentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
38
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 20 publications
(31 reference statements)
10
38
2
Order By: Relevance
“…In this case-control study chosen to evaluate the effectiveness of SMC administered in a mass campaign in Senegal, the same difficulties as those described by Cairns et al, and related to the rigor required for this type of study, were encountered 9 . The usefulness of case-control studies for determining the efficacy of SMC as well as that of a vaccine has been reported.…”
Section: Discussionmentioning
confidence: 96%
“…In this case-control study chosen to evaluate the effectiveness of SMC administered in a mass campaign in Senegal, the same difficulties as those described by Cairns et al, and related to the rigor required for this type of study, were encountered 9 . The usefulness of case-control studies for determining the efficacy of SMC as well as that of a vaccine has been reported.…”
Section: Discussionmentioning
confidence: 96%
“…12 Pooled estimates across seven studies in SSA indicate that SMC implementation reduces the incidence of clinical malaria during the first 4 weeks by about 88%. 13 Since 2012, 13 countries in the Sahel region of Africa have implemented SMC and over 33 million children were protected by the intervention in 2020 alone. 14 For SMC, caregivers administer three doses of the drug, sulfadoxine-pyrimethamine plus amodiaquine, over a 3-day period for up to 5 months of the rainy season.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…To protect children from malaria, in 2012, the WHO recommended seasonal malaria chemoprevention (SMC) in areas of highly seasonal malaria transmission during the rainy season, during periods when malaria incidence is at the highest 12. Pooled estimates across seven studies in SSA indicate that SMC implementation reduces the incidence of clinical malaria during the first 4 weeks by about 88% 13. Since 2012, 13 countries in the Sahel region of Africa have implemented SMC and over 33 million children were protected by the intervention in 2020 alone 14…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with WHO recommendations, malaria prevention in Mali involves vector control using LLINs and IRS and chemoprevention in children and pregnant women [ 10 ]. A major control intervention is seasonal malaria chemoprevention (SMC) [ 11 ], which consists of the monthly administration of antimalarial drugs to children aged 3–59 months during the high malaria transmission season [ 12 ]. Since 2016, the NMCP has been implementing SMC interventions in all health districts on the basis of historical national data on malaria incidence or prevalence [ 13 ].…”
Section: Introductionmentioning
confidence: 99%